STRUKTUR NARATIF CERITA RAKYAT SUMBAWA BARAT - Alaini, Nining Nur (ATAVISME, 2014)
Oral literature will always change according to the dynamic of their community. Some oral literary works in Indonesia are extinct already due to not yet documented. Oral literature is, actually, a cultural treasure of Indonesia able to show the rich variety of cultures and values and the incredible creativity of their community. Change and the loss of a variety of oral literature mean the extinction or change of property contained in them. One form of Indonesian oral literature still enjoyed today is folklores of West Sumbawa. Therefore, this study aims to document the oral literature of West Sumbawa in the form of folklores. Furthermore, the folklores collected will be analyzed by using Vladimir Propp?s theory of narrative structure. The result shows that the folklores of West Sumbawa have fourteen actor functions. The fourteen functions can be distributed into five environmental actions. Oral literatures will always change according to the dynamic of their community. Some oral literary works in Indonesia are extinct already due to not yet documented. Oral literature is, actually, a cultural treasure of Indonesia able to show the rich variety of cultures and values and the incredible creativity of their community. Change and the loss of a variety of oral literature mean the extinction or change of property contained in them. One form of Indonesian oral literature still enjoyed today is folklores of West Sumbawa. Therefore, this study aims to document the oral literature of West Sumbawa in the form of folklores. Furthermore, the folklores collected will be analyzed by using Vladimir Propp?s theory of narrative structure. The result shows that the folklores of West Sumbawa have fourteen actor functions. The fourteen functions can be distributed into five environmental actions. Key Words: oral literature; folklore; narrative structure Abstrak: Kehidupan sastra lisan akan selalu berubah sesuai dengan dinamika komunitas pemiliknya. Ada beberapa sastra lisan di Indonesia, yang telah hilang karena belum didokumentasikan, sedangkan sastra lisan adalah kekayaan budaya Indonesia yang kaya akan khazanah kearifan lokal dan merupakan kreativitas yang luar biasa dari komunitas pemiliknya. Perubahan dan hilangnya sastra lisan berarti punahnya kearifan lokal dan khazanah budaya yang terkandung di dalamnya. Salah satu bentuk sastra lisan Nusantara yang masih hidup hingga saat ini adalah cerita rakyat Sumbawa Barat. Cerita rakyat yang berhasil didokumentasikan dikaji struktur naratifnya berdasarkan pada struktur naratif yang dikemukakan oleh Vladimir Propp. Penelitian ini akan mendokumentasikan sastra lisandari Sumbawa Barat yang berwujud cerita rakyat. Dari hasil kajian yang telah dilakukan, dapat disimpulkan bahwa cerita rakyat Sumbawa Barat memiliki empat belas fungsi pelaku. Keempat belas fungsi pelaku tersebut dapat didistribusikan ke dalam lima lingkungan tindakan